KEBUNTUAN PEMAHAMAN TERHADAP POLEMIK WACANA ISLAM NUSANTARA: KAJIAN DARI PERSPEKTIF MAKNA PRAGMATIK - Taufik Nurhadi (Universitas PGRI Adi Buana Surabaya, 2020)
This study is aimed at describing of the impasse understanding of the polemic of the Nusantara Islamic discourse. The data were in the form of Indonesian language used in the polemic of the pros and cons of the Nusantara Islam issue, which is published on social media, Youtube. Data collection uses the method of listening with tapping, SBLC, download, and note techniques. The data analysis method used is Constant Comparative Analysis. The results of the analysis showed that there was a deadlock in understanding the issues of the Nusantara Islamic discourse regarding 4 things, namely symbolic identity, rejection in terms of terms, classic rivalry between tribes, and culture as the core problem. The deadlock of understanding was triggered by long competition between the two circles of Muhammadiyah and Nahdatul Ulama in viewing worship practices from different perspectives.